Who is a Nuisance? Criminal Activity Nuisance Ordinances in Ohio - Andrasik, Kristi (2017)
Criminal Activity Nuisance Ordinances (CANOs) are local laws found in thousands of cities throughout the country which penalize property owners if repeated incidents of criminal activity related to their property occur over a set period of time (typically, 12 months). Nearly 50 cities in Ohio have CANOs, including more than 20 in Northeast Ohio.Drawing on extensive public records from a sample of Northeast Ohio cities, this report offers a snapshot of CANOs and how they are being used. • CANOs disproportionately impact renters, people using housing vouchers, and people of color. • Race and class stereotypes surface in public discussions of CANOs, and are sometimes invoked to justify the establishment or enhancement of CANOs • CANOs are frequently applied beyond their scope to target minor, non-criminal behavior • Many cities across Ohio put survivors of domestic violence at heightened risk of eviction by defining domestic violence as a “nuisance activity”; in some cities, more than half of CANO letters are sent in response to domestic violence incidents• If emergency services are sent to a home in response to a call made to a suicide hotline, that property can be deemed a nuisance • Seeking medical assistance for someone experiencing a drug overdose crisis is a common reason that properties are placed on a nuisance list • It is often difficult or even impossible for a property owner or tenant to challenge a mistaken nuisance designationWhile the findings presented in this report center on Northeast Ohio, residents in the thousands of other cities with CANOs across the country may be experiencing similar impact. We encourage policymakers, researchers, and community stakeholders to use this report to inform deeper conversations on the implications of CANOs, and to expand research on the use and consequences of these laws